Enhanced four-wave mixing efficiency of BI-EDF in a new ring configuration for determination of nonlinear parameters - Shahi, S.; Harun, S. W.; Lim, K. S.; Naji, Ahmed Wathik; Ahmad, H. (2009)
This paper demonstrates a four-wave mixing (FWM) effect in the reduced length of Bi-based erbium-doped fiber (Bi-EDF) with both open and ring configurations. The generated FWM signals are used to determine the nonlinear properties of the Bi-EDF based on two CW dual-wavelength measurement methods. The unique and practical benefits of the use of the highly nonlinear Bi-EDF in a ring cavity are experimentally demonstrated to enhance the FWM efficiency. By employing this method, the nonlinear parameter of γ and nonlinear index coefficient of n2 for the 215 cm long Bi-EDF are estimated to be 59.16 (W-1 km-1) and 4.40 × 10-19 (m2/W) respectively at 1612 nm. n2 value per effective area Aeff is estimated to be 1.51 × 10-8 (W-1). Empirical comparison shows that the values found by theoretical model are both in good agreement with the experimental one and much higher than that of silica.